Investigation of the crust in the southern Karoo using the seismic reflection technique - Loots, Letticia (My University, 2014)
Several seismic reflection surveys were conducted in the late 1980s and early 1990s under the auspices of the SA National Geophysics Programme. These surveys targeted the Bushveld Complex, Limpopo Mobile Belt (Limpopo Province), Witwatersrand Basin, Vredefort Dome and the Beattie magnetic anomaly (BMA) in the Southern Karoo. The ~100 km seismic reflection profile described in this study (SAGS-03-92) covers the BMA, the Southern Cape Conductive Belt (SCCB) and the Karoo/Cape Fold Belt boundary. The profile runs from approximately Droëkloof in the south to Beaufort West in the north along the N12 national road. The profile was acquired in 1992, but the complete profile was not interpreted or published prior to this study. The purpose of this study is to successfully reprocess the data and to do a structural and stratigraphic interpretation in order to try and understand the geological history and processes that led up to the formation of the rocks in that area. SAGS-03-92 reveals a clear image of the crust in the southern Karoo. The crust is interpreted to be around 37 km thick in the area of investigation and can be classed into three parts: upper crust, middle crust and lower crust. The upper crust consists of the Karoo and Cape Supergroup rocks that dip slightly to the south. This interpretation has been confirmed by two deep boreholes (BH No. 3 and KW 1/67). The seismic fabric shows quite a strong character in the upper crust and the interpreted boundaries between the different lithologies (The Table Mountain, Bokkeveld and Witteberg Groups of the Cape Supergroup and the Dwyka, Ecca and Beaufort Groups of the Karoo Supergroup) are for the most part quite easy to identify. Within the Cape Fold Belt (CFB), however, the seismic character becomes distorted in such a way that it is very difficult to make out any features. This is possibly due to the severe faulting and folding that occurred when the CFB formed. An unconformity that can continually be followed throughout the profile (although it disappears in the south of the profile possibly due to deformation when the CFB formed) separates the upper crust from the middle crust and the unconformity is clearly indicated by a strong series of reflectors on the seismic profile. The middle crust is interpreted to consist of granitic-gneisses belonging to the Bushmanland Terrane (part of the Namaqua-Natal Belt (NNB)). The seismic profile suggests that the NNB gneisses continue beneath the Cape Fold Belt. The seismic fabric dips steeply to the north. The middle crust also hosts the source of the Beattie Magnetic Anomaly (BMA). There is an area of high reflectivity under the BMA on the seismic profile that differs significantly from the surrounding seismic character. This area is characterised by a beanshaped cluster of strong reflections dipping north and south. It is ~10 km wide, with a thickness of ~8 km and occurs at a depth of ~6 km to ~10 km. The lower crust is interpreted to consist of either granites belonging to the Areachap Terrane, Richtersveld or Kheis Province (NNB) or rocks belonging to the Kheis Province. The seismic fabric of the lower crust dips moderately to the south. The Moho is recognised at ~37 km depth at ~68 km from the south of the profile, but for the rest of the profile, it is unclear where the Moho is encountered. The research done for this study correlates well with work done under the auspices of Inkaba yeAfrica, especially the work done by Ansa Lindeque
Keywords: Earth - Crust.; Geology - South Africa - Karoo.; Seismic reflection method.